Bahasa Inggris - Hariance, Rika; Noer, Melinda; Ridwan, Endrizal; Hasnah, Hasnah (Jurnal AGRISEP, 2023)
Cooperatives are suitable institutions to coordinate and manage the resources that owned by smallholders. To be sustainable, the formation of cooperatives must be based on individual awareness through collective action. To find out the most influencing factors for smallholder tea plantation farmers to join cooperatives, research was conducted on farmers who are members of the Eleven Jurai Saiyo Organic Tea Producers Cooperative which is abbreviated as KPTO-SJS. By using a quantitative descriptive method, the survey was conducted by snowball sampling to 30 members of the cooperative, then the data was analyzed using the SEM-PLS analysis tool with Confirmatory Factor Analysis. The results showed that all variables significantly affect the awareness of farmers to join the cooperative. However, the most influential factor is the knowledge factor with a path coefficient value of 0.576, followed by characteristics, social factors and economic factors. Because all variables have a positive influence on farmers' decisions to join cooperatives, an increase in each variable will have an effect on increasing the number of farmers joining cooperatives.  So increasing farmers' knowledge is a must to improve farmers' ability to make decisions.